Evidence-based interventions for children with challenging behavior - Armstrong, Kathleen (Kathleen Hague); Ogg, Julia A.; Sundman-Wheat, Ashley N.; St. John Walsh, Audra (New York : Springer, 2014)
When a child has difficulties eating or sleeping, or throws frequent tantrums, many parents cross their fingers and hope it's a phase to be outgrown soon. But when they persist, challenging behaviors can follow children to school, contributing to academic problems, social difficulties, and further problems in adolescence and adulthood. The authors of Evidence-Based Interventions for Children with Challenging Behavior take a preventive approach in this concise, well-detailed guide. Offering best practices from an extensive Response to Intervention (RTI) evidence base, the book provides guidelines for recognizing the extent of feeding, sleeping, toileting, aggression, and other issues, and supplies successful primary, secondary, and tertiary interventions with rationales. Case examples integrate developmental theories and behavior principles into practice, illustrate how strategies work, and show how to ensure that parents and caregivers can implement them consistently for maximum effect. Progress charts, content questions, and other helpful features make this an invaluable resource for students and professionals alike. Included in the coverage: The prevention model and problem solving. Screening techniques. Evidence-based practices with children and their caregivers. Behavior principles and their application. Monitoring progress and evaluating outcomes. Plus helpful appendices, resource links, and other learning tools. Evidence-Based Interventions for Children with Challenging Behavior is an essential text for graduate students, scientist-practitioners/professionals, and researchers in child and school psychology; assessment, testing and evaluation; occupational therapy; family; educational psychology; and speech pathology.
Chapter 1: Common Early Childhood Behavior Problems -- Chapter 2: Early Childhood Development Theories -- Chapter 3: The Prevention Model and Problem Solving -- Chapter 4: Screening Techniques -- Chapter 5: Evidence-Based Practices with Children and their Caregivers -- Chapter 6: Behavioral Terms and Principles -- Chapter 7: Applying Principles of Behavior -- Chapter 8: Progress Monitoring -- Chapter 9: Evaluating Outcomes -- Chapter 10: Summary & Conclusions of Best Practices in Providing Services for YCCB -- Appendix A: Developmental Milestones References -- Appendix B: ABC Chart for Determining a Behaviors Function -- Appendix C: HOT DOCS Behavior Chart -- Appendix D: Graphing by Hand -- Glossary.
Includes bibliographical references (pages 207-219) and index.
Keywords: Child behavior; Behavior therapy -- Methods; Behavioral Symptoms -- therapy; Child; Evidence-Based Practice -- methods; Behavior disorders in children; Behavior disorders in children -- Treatment